Cavity behind Special Segment Structures in Upward Shield Tunneling: A Numerical Approach - Xinjiang Wei; Liangliang Lu; Xiao Wang; Zihai Yan; Jiajia Yan (Advances in Civil Engineering)
Proper design of special segments under cavity conditions is essential for successfully implementing the upward shield tunneling method. When constructing upward tunnels, the segment structure in the corresponding construction area of the horizontal tunnel is special. To study the internal force distribution on the structure under the worst possible conditions given by the upward shield tunneling method, MIDAS GTS NX software is used to numerically simulate the structure based on the condition of the cavity behind it to determine the most unfavorable radius of the cavity. Moreover, an analysis of the cavity location is conducted. The results demonstrate that when the cavity is located at the bottom of the arch with a radius of 1 m and near the top of the arch with a radius of 0.5 m, the special segment structure is under the most unfavorable combination of stresses. The most dangerous working condition occurs when there is a 0.5 m radius cavity on one side of the arch in the cross-section of the special segment.